Risk Factors Of Stroke: Literature Review - Oliveira, Adirson Barbosa de; Muhith, Abdul; Zahro, Chilyatiz (Journal of Applied Nursing and Health, 2023)
Background: Stroke is the most common cause of disease in the world and is the highest cause of death in Indonesia, so prevention is very important to minimise the incidence of stroke. The most appropriate effort to prevent stroke is to control stroke risk factors. The purpose of the literature review is to analyse the risk factors associated with stroke events in patients. Methods: The method used is a literature review using a journal database from Pubmed, Science Direct, and Google Scholar. In the 2019-2023 range, with the keywords "stroke, factors causing stroke", and stroke, 220 articles were obtained Results: Search for articles according to the criteria and obtain ten articles that are ready to be reviewed. These articles explain the risk factors for stroke. It is hoped that stroke patients will try to control stroke risk factors Conclusion: This literature review shows that the risk factors for stroke are increasing due to a history of diseases such as hypertension, diabetes mellitus, age, gender, high cholesterol, obesity, lack of public knowledge about stroke and consumption of alcohol, smoking and drugs, including a lifestyle